The role of dismissal protection in personnel management: From the point of view of personnel managers - Florian Schramm; Michael Schlese (Management Revue, 2007)
This article concerns itself with the effects of dismissal protection on personnel management behaviour within companies. The basis of the empirical analysis is 41 expert interviews conducted in 2006 as well as information available from a standardised survey of 750 personnel managers which was carried out in 2007. As a whole the effects of dismissal protection on personnel management are perceived by personnel managers to be insignificant. In general, employment law is considered to be a necessary framework which is, for the most part, non-obstructive yet at the same time nonsupportive. Negative judgements relating to dismissal protection referred to its possible prohibitive effects (in the context of new-hirings), company-internal effects (in the context of confrontations within the company) and preventive effects (in the context of the dismissal of personnel). The prohibitive effect in the form of the non-hiring of new employees or the turning to other forms of employment rather than full time is rather weak. The decision to avoid hiring new employees is dependent upon the personnel manager's perception of employment law and not so much on an economical framework or the characteristics of the organisation. The role of dismissal protection within the company is also quite limited. In particular, having been employed by the company for a long time is considered very important for business management reasons. The judgements of those responsible for personnel are not to be explained with clear situational variables such as the business situation of the company or the development of the company's number of employees. There seems to be, rather, quite a lot of leeway regarding the understanding of Employment law and that this is dependent on the personnel managers' competence in this area as well as other factors. These findings are also relevant in light of the announced harmonisation with the European Labour Court (Green Paper labour law).
Keywords: 650; dismissal protection; perception; personnel manager; Personalmanagement; Personalführung; Führungskräfte; Kündigungsschutz; Deutschland